Zum Stand der Staatsschuldenkrise in Europa - Heinz-Dieter Smeets (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2012)
– The euro countries currently experience a severe government debt crisis. Since Greece asked for financial assistance in May 2010 there has been a lively debate on how to resolve this situation. The solution that has been primarily suggested by politicians so far is to finance governments' financial needs through emergency credits from EU sources (EFSF/ESM) and the International Monetary Fund. After explaining provisions like the stability pact and risk premiums on interest rates which aimed at guaranteeing fiscal stability in the pre-crisis EMU an overview is given showing financial and other political reactions to the crisis. In a second step, the sustainability of the Greek debt situation is extensively analyzed by employing the government budget constraint. The necessary primary surpluses enabling Greece to finance its government debt without international support from 2020 onwards are, however, substantial. Therefore, it is very likely that Greece either needs further financial assistance or an additional hair cut. Finally, some suggestions are made how to avoid possible government debt crises in the future.
Keywords: 330; Staatsschuldenkrise; Schuldentragfähigkeit; Bankenrekapitalisierung; Währungsunion; Euro; Öffentliche Schulden; Europäischer Stabilitätsmechanismus; Nachhaltigkeit; Eurozone; Staatsbankrott; Griechenland